An implementation plan for total productive maintenance (TPM) in a palm mill factory [electronic resource] - 332526 Mohamed Helmy Maarof (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2007